Location or size? A finite element analysis study of necrotic lesion impact on femoral head collapse - Shun Lu; Tianye Lin; Longfei Han; Ziqi Li; Mingcong He; Qiushi Wei (Journal of Orthopaedic Surgery and Research)
Abstract Background The location and size of necrotic lesions are important factors for collapse, The preserved angles (PAs) are divided into anterior preserved angle (APA) and lateral preserved angle (LPA), which could accurately measure the location of necrosis lesion. We used them to evaluate the effect of the location and size of necrotic lesions on collapse by finite element analysis, to offer a framework for evaluating the prognosis of osteonecrosis of the femoral head (ONFH) in clinical settings. Methods 3 left hip models were constructed based on CT data. Within each hip model, three necrosis lesion models were modeled, with necrotic tissue volumes of 30%, 50%, and 70% repectively. The ONFH models with LPA of 45.5°, 50.5°, 55.5°, 60.5°, 65.5°, 70.5°, and 75.5° when APA was 60.5°, and ONFH models with APAs of 45.5°, 50.5°, 55.5°, 60.5°, 65.5°, 70.5°, and 75.5° when LPA was 60.5° were Constructed. The maximum von Mises stess of the femoral head and necrotic lesion, as well as the femoral head displacement, were calculated to evaluate the biomechanical effects of these models. Results (1) In models with the same necrotic volume, when APA was 60.5°, the indexes of the LPA < 60.5° models were significantly higher than those of the LPA ≥ 60.5° models (P < 0.05); the differences of the indexes among the LPA ≥ 60.5° models were not statistically significant (P > 0.05). (2) When LPA was 60.5°, the indexes of models with APA < 60.5 ° and APA ≥ 60.5 ° show the same trend as the former. (3) In the models with the same PAs, there was no statistically significant difference in the indexes (P > 0.05). Conclusion The location of the necrotic lesion exerts a greater impact on femoral head collapse compared with the size of the lesion. The location of the necrosis may deserve more consideration when assessing the risk of collapse in patients with early onset ONFH.